The Influence of Celebrity Endorsers on Social Media Instagram on Interest in Buying Scarlett Products(Study on Community in Makassar District, East Jakarta) - Oktaviani, Dwi Nur; Narsih, Dwi (Publikasi Inspirasi Indonesia, 2023)
The purpose of this research is to find out whether there is an influence of Celebrity Endorser on Instagram social media on the Buying Interest of Scarlett Whitening products in the community in the Kec. Makassar, East Jakarta. The population taken in this study is the people who live in the area of RT 006 RW 013 totaling 282 people. The number of samples as many as 70 people were taken using a non-probability sampling technique with a purposive sampling technique. Methods of collecting data using a questionnaire (questionnaire) and literature study. The calculation results obtained from the equation of Simple Linear Regression Analysis Y=6.710+0.717 X with a constant value of a of 6.710 and a value of b of 0.717 meaning that there is an influence between Celebrity Endorser on Purchase Interest. The results of the calculation of the correlation coefficient of 0.439 indicate that there is a moderate relationship between Celebrity Endorser and Purchase Interest. The coefficient of determination is 19.27%, this means that Celebrity Endorser contributes 19.27% to Purchase Interest, while the remaining 80.73% is the contribution of other factors not examined by the author. The results obtained from hypothesis testing with = 5% with the results > (4,301 > 1,995) then 0 is rejected and 1 is accepted, it can be concluded that there is an influence between variable X (Celebrity Endorser) on variable Y (Buying Interest) in the District Area Makassar, East Jakarta.